A Victimological Analysis of Terrorism Victims in the Indonesian Criminal Justice System - Alberto Paskah Tarigan; Suci Ramadani; Bima Agung Wibowo; Andronius Basado Siahaan (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Terrorism is an extraordinary crime with multidimensional impacts; it not only causes material losses, but victims are also those who directly suffer as a result of the crime—physically, psychologically, economically, and socially. However, in the practice of the criminal justice system, victim protection tends to be neglected because law enforcement focuses primarily on the perpetrators. As a result, victims are often treated merely as witnesses and have not yet received optimal fulfillment of their rights. This study aims to examine the concept of victim protection from a victimological perspective and to analyze the status and role of victims within the criminal justice system. This study examines the state’s responsibility toward victims of terrorism from both a victimological and criminal law enforcement perspective. The primary focus of the study is how the state fulfills its obligations to provide protection, rehabilitation, and the fulfillment of the rights of victims of terrorism, both legally and socially. The research method employed is normative legal research using a legislative and conceptual approach, utilizing primary, secondary, and tertiary legal sources. The results of the study indicate that victimology views victims as legal subjects entitled to protection, recognition, and compensation for losses. Victim protection encompasses not only legal aspects but also physical and psychological protection, as well as the prevention of victimization.